The caregiver in the assistance setting - de Oliveira Duarte, Yeda Aparecida (O Mundo da Saúde, 2006)
This article describes the consensus related to the caregiver’s activities in behalf of people with disability and the legal aspects involved, specially in the nursing area. It delineates a panorama about the main points that had encouraged the emergence of this “character” today very important in the assistance setting. It tries to elucidate the polemic points involving nursing and caregivers and describe the discussions developed with different actors in the health area.